The horse doctor is in : a Kentucky veterinarian's advice and wisdom on horse health care - Kelley, Brent P. (North Adams, MA : Storey Books, 2002)
A veterinarian presents practical advice on equine diseases, lameness, breeding and foaling, and care and management, sharing true stories about his encounters with horses, owners, trainers, and breeders.
Includes index.
Booklist, November 2002
Young Adult
Keywords: Kelley, Brent P; Horse Diseases -- therapy; Animal Husbandry; Horses -- Diseases -- Anecdotes; Horses -- Health -- Anecdotes; Veterinary medicine -- Anecdotes; Veterinarians -- Anecdotes